Unequal weight: equity oriented policy responses to the global obesity epidemic - Friel, Sharon (BMJ Publishing Group Ltd., 2007)
The health professions need to spearhead a concerted intersectoral response to obesity, say Sharon Friel, Mickey Chopra, and David Satcher